OP20 Doctors' perspectives on adhering to advance care directives when making medical decisions for patients with chronic disease:an australian interview study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Detering, K; Moore, N; Low, T; Nolte, L; Sellars, M
Abstract : Background: Advance care planning (ACP) assists people to identify their goals, values and treatment preferences for future care. Ideally documentation in an advance care directive (ACD) occurs. ACDs are used when treatment plans are developed for non-competent patients. Limited studies have explored perspectives of doctors regarding adherence to ACDs during medical decision-making for patients. Aim: To describe the perspectives and attitudes of doctors on adhering to ACDs. Methods: Doctors were recruited using convenience sampling. Face-to-face semi-structured interviews were conducted, audiotaped, transcribed and analysed using thematic analysis. Interviews explored 3 case scenarios; doctors were asked to provide treatment plans. They were then given a values-based, followed by a treatment-based ACD. Prompting was used to understand how (if at all) the ACD influences treatment, and reasoning for decisions. Results: 21 doctors; median: 10 years experience; were included. Interviews lasted 10–60 minutes. Most doctors reported experience with ACP and ACDs. 3 major themes were identified: aligning with patient preferences (alleviating burden of decision-making, returning to baseline health, clarifying with others), questioning validity (distrusting patients' decision-making ability, navigating unrealistic goals, reaching ceiling of care) and navigating decisional conflict (prioritising best interest of the patient and overcoming family opposition). Conclusion: ACDs provide doctors with opportunities to align patient preferences with treatment; however, doctors sometimes question the validity of ACDs and experience decisional conflict when attempting to adhere to ACDs in practice, especially when family members oppose the plan. These results will assist development of clinical education programs, and resources supporting completion of more specific ACDs.